The Coming Trump-Putin Summit - Cheang, Chris (2018)
Following his summit in Singapore with Kim Jong Un, Trump now turns to Russia’s leader Vladimir Putin. Their high-level encounter this month might provide the basis for some tangible movement to ease bilateral tensions. They could well make bold, unexpected moves to stabilise relations